Tourists' Engagement on Tourism Organizations' Facebook Pages: The Role of User-Generated Content - Santos, Sara (2023)
Tourism industry prospects are presented by digital marketing and consumer travel behaviour changes. Given this fact, digital content marketing (DCM) assumes greater significance for enhancing social media user engagement. Providing valuable and relevant information that differentiates the company and catches the consumers' attention has been one of the current challenges in this area. The wide availability of information on the Internet changes how consumers engage with it. Therefore, creating and disseminating educational and pertinent content is now mandatory. To ensure the effectiveness of the process, it is crucial to understand with whom, how, when, and where communication will be carried out. Thus, tourism organisations must offer targeted, tailored, and appealing information to interest customers more about the destinations. Social media is a commonly used strategy for tourism promotion initiatives, where User Generated Content (UGC) has emerged as one of the most popular means to achieve this goal. “Turismo Centro de Portugal” is responsible for publicizing the Centre region of Portugal, including cities such as Coimbra, Aveiro, Viseu, and Leiria. Turismo Centro de Portugal has won several communication-related awards, having already been recognized internationally for its advertising campaigns. Numerous studies analyzing user-generated content and digital content are available, but they invariably look at businesses rather than tourism-related institutions. Hence, conducting a study to identify follower engagement and involvement in digital content marketing posts versus user-generated content posts applied to the Turismo Centro de Portugal was considered pertinent. For this purpose, a qualitative analysis of the existing content and its results on Turismo Centro de Portugal's Facebook page was developed based on a social media content analysis framework adapted from other authors. The results revealed the importance of using user-generated content in a social media communication strategy for tourism organisations.